Risk Quantification and Allocation Methods for Practitioners - Belles-Sampera, Jaume; Guillén, Montserrat; Santolino, Miguel (Amsterdam University Press, 2021)
Risk Quantification and Allocation Methods for Practitioners offers a practical approach to risk management in the financial industry. This in-depth study provides quantitative tools to better describe qualitative issues, as well as clear explanations of how to transform recent theoretical developments into computational practice, and key tools for dealing with the issues of risk measurement and capital allocation.